The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/09593985.2019.1572846
|View full text |Cite
|
Sign up to set email alerts
|

The perceptions of older adults living with chronic musculoskeletal pain about participating in an intervention based on a behavioral medicine approach to physical therapy

Abstract: Background There is evidence that interventions based on a behavioral medicine approach to physical therapy (BMPI) are beneficial for older adults living with chronic pain; however, knowledge of the perceptions of older people regarding their participation in BMPI is lacking. Aim The aim of this study was to describe the perceptions of older people about being participants in a home-based BMPI. Methods Semi-structured interviews were conducted with 12 older adults living with chronic pain and participating in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 34 publications
7
15
0
Order By: Relevance
“…The results of the present study are in line with the results from a recently published qualitative study evaluating how older adults perceive to participate in a BMPI and their perceived gains. The gains of the intervention were by the informants described in physical, psychological, social, and functional terms and enabling participants to live at home for longer 51. Finally, the results support the hypothesis of the study protocol, whereby BMPI can be a suitable evidence-based intervention for community-dwelling older adults living with chronic musculoskeletal pain 15…”
Section: Discussionsupporting
confidence: 60%
“…The results of the present study are in line with the results from a recently published qualitative study evaluating how older adults perceive to participate in a BMPI and their perceived gains. The gains of the intervention were by the informants described in physical, psychological, social, and functional terms and enabling participants to live at home for longer 51. Finally, the results support the hypothesis of the study protocol, whereby BMPI can be a suitable evidence-based intervention for community-dwelling older adults living with chronic musculoskeletal pain 15…”
Section: Discussionsupporting
confidence: 60%
“…The present study revealed that the OEP seems to promote "age in place" in terms of improved physical function, mastering of everyday activities, improved self-efficacy, and a higher degree of independence. This finding is in line with that of a recently published study about an intervention focusing on exercise and behavior change for older adults living with chronic pain (Cederbom, Nortvedt, and Lillekroken, 2019). Promotion of "aging in place" is of high clinical relevance, as this is the main goal for all interventions that healthcare professionals conduct in their daily practice (Cederbom, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, the description that the OEP is easy to individualize and adapt to older adults' physical abilities is very encouraging, particularly given that these factors have been proven to promote adherence to exercise among this target population (Cederbom et al, 2014b;Manor and Lipsitz, 2013). Other crucial factors in the context of promoting adherence are that the intervention is performed in an environment that is suitable for the individual and that it provides available support (Arkkukangas et al, 2017;Cederbom, Nortvedt, and Lillekroken, 2019;Jiménez-Beatty Navarro et al, 2007), which the present study confirmed. Moreover, when implementing the OEP in clinical practice, the present study's findings show how important it is to carefully customize and adapt the support of PTs based on the older person's needs, such as the number of home visits and support by telephone.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations